2019
DOI: 10.1152/ajplung.00302.2018
|View full text |Cite
|
Sign up to set email alerts
|

Vascular TSP1-CD47 signaling promotes sickle cell-associated arterial vasculopathy and pulmonary hypertension in mice

Abstract: Pulmonary hypertension (PH) is a leading cause of death in sickle cell disease (SCD) patients. Hemolysis and oxidative stress contribute to SCD-associated PH. We have reported that the protein thrombospondin-1 (TSP1) is elevated in the plasma of patients with SCD and, by interacting with its receptor CD47, limits vasodilation of distal pulmonary arteries ex vivo. We hypothesized that the TSP1-CD47 interaction may promote PH in SCD. We found that TSP1 and CD47 are upregulated in the lungs of Berkeley (BERK) sic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 81 publications
0
38
0
Order By: Relevance
“…Direct confirmation of vasoocclusion in sickle mice is challenging, and typically limited to the finding of vascular congestion with large numbers of sickled RBCs. 51 In a postmortem study of a patient with SCD who died during a VOE, the bone marrow histology showed dilated and engorged small vessels which were not completely occluded by sickled RBCs, a possible fixation artifact. 52 In our experiments, it is likely that restoration of vascular patency and blood flow may have occurred by the time the organs were harvested 24 hours after LPS challenge, a prespecified time point required by our imaging protocol, thus precluding us from detecting earlier microvascular obstructions and their attendant ischemic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Direct confirmation of vasoocclusion in sickle mice is challenging, and typically limited to the finding of vascular congestion with large numbers of sickled RBCs. 51 In a postmortem study of a patient with SCD who died during a VOE, the bone marrow histology showed dilated and engorged small vessels which were not completely occluded by sickled RBCs, a possible fixation artifact. 52 In our experiments, it is likely that restoration of vascular patency and blood flow may have occurred by the time the organs were harvested 24 hours after LPS challenge, a prespecified time point required by our imaging protocol, thus precluding us from detecting earlier microvascular obstructions and their attendant ischemic changes.…”
Section: Discussionmentioning
confidence: 99%
“…157 Finally, in a model of sickle cell disease-associated PH severity of pulmonary vascular disease correlated with levels of CD47. 158 This study also demonstrated that mice with myeloid cell deficiency of CD47 were conferred protection against development of PH, associated with decrease ROS generation and a decreased DNA damage response. Thus, CD47 regulation through cytosolic DNA sensing in innate immune cells remains a plausibleā€”and thought-provokingā€”novel method of treating the underlying pathophysiology predisposing to pulmonary vascular disease.…”
Section: Exposures and Therapymentioning
confidence: 62%
“…Supporting empiric data demonstrated normalization of pulmonary pressures in CD47 -/mice, as well as ex vivo demonstration of decreased ET-1 production by human pulmonary artery endothelial cells treated with a neutralizing CD47 antibody 157 . Finally, in a model of sickle cell diseaseassociated PH severity of pulmonary vascular disease correlated with levels of CD47 158 . This study also demonstrated that mice with myeloid cell deficiency of CD47 were conferred protection against P e e r R e v i e w V e r s i o n development of PH, associated with decrease ROS generation and a decreased DNA damage response.…”
Section: Cd47 Blockadementioning
confidence: 92%
“…TSP-1 has previously been implicated in the pathophysiology of vascular occlusion and pulmonary hypertension associated with sickle cell disease (SCD) [ 53 , 54 ]. Increased prothrombotic risk in SCD is linked to elevated TSP-1 levels, which not only inhibit ADAMTS13 proteolysis of von Willebrand Factor [ 55 ], but also provoke RBC MP shedding; this process, in turn, favors RBC adhesion to endothelial cells as well as stimulation of endothelial cell apoptosis [ 56 ].…”
Section: Discussionmentioning
confidence: 99%